Identification of Medicinal Plants on the Basis of Morphological Observation of Seeds in the Region of Sétif, Algeria - Hani, Meriem; Merghem, Mounira; Lebazda, Rafika (Asian Journal of Biological and Life Sciences)
Present study has been carried out on the identification of medicinal plants on the basis of morphological observation of seeds in the region of Sétif, Algeria. The analyzed characters in which the study was based on are: shape, color, size (length, width), solidity, surface, weight of 100 seeds. The results showed that seeds were laterally compressed and bilobed and showed morphological variations in size, shape, color, seed coat ornamentation. Shape of seeds showed a large variation among the investigated species. Most of seeds have elongated ovoid shape (Linum usitatissimum L., Cupressus sempervirens L., Pinus halepensis Mill., Lepidium sativum L…..) and others are Linear (Hordum vulgare L., Avena sterilis L….) or ovoid (Rhus coriaria L., Salvia hispanica L.. ). Color varies from yellow to brown, brown to dark brown, light creamy, white, orang, grayish, black dark and reddish. Seed dimensions vary greatly among the examined species, the largest seeds in Cuperus rotundus L. have a length of 12.62±0.48 mm, and the smallest seeds measure 0.75±0.11mm in Portulaca oleracea L. Highest weight was observed with seeds of Zea mays L. (1525.20±36.20 mg), while lowest weight was found in seeds of Portulaca oleracea L. (0.59±0.04 mg). Seed morphological characteristics proved to be useful taxonomic features, helpful in identification of large number of species and genera. Seed characters, such as shape, size and seed-coat surface, have low phenotypic plasticity and are less affected by environmental conditions. The purpose of this study was to describe and compare external seed morphological characteristics of 33 medicinal plants species, and to evaluate their possible use for taxonomic considerations.
Keywords: Color.; Medicinal plants; Morphological observation; Seeds; Shape